2021
DOI: 10.1021/acsnano.1c04269
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Modulation of Excitonic Properties in Monolayer WSe2 under Strong Dielectric Screening

Abstract: We investigate the interaction of excitons in monolayer WSe 2 with the piezoelectric field of surface acoustic wave (SAW) at room temperature using photoluminescence (PL) spectroscopy and report a large in-plane exciton polarizability of 8.43 ± 0.18 × 10 −6 Dm/V. Such large polarizability arises due to the strong dielectric screening from the piezoelectric substrate. In addition, we show that the exciton-piezoelectric field interaction and population distribution between neutral excitons and trions can be opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…A thin layer of indium-tin-oxide (ITO) was deposited on the heterostructure region as a top transparent electrode. This top electrode plays an important role by efficiently suppressing the in-plane piezoelectric field component (E x ), which may cause exciton dissociation 14,[41][42][43] , while maintaining a relatively strong out-of-plane field component E z . The finiteelement method (FEM) simulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A thin layer of indium-tin-oxide (ITO) was deposited on the heterostructure region as a top transparent electrode. This top electrode plays an important role by efficiently suppressing the in-plane piezoelectric field component (E x ), which may cause exciton dissociation 14,[41][42][43] , while maintaining a relatively strong out-of-plane field component E z . The finiteelement method (FEM) simulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the interim of our review process we became aware of similar experiments reported for acoustic transport in WSe 2 MLs at room temperature …”
mentioning
confidence: 82%
“…This implies a practical approach for tuning the electrical properties in advanced electronic devices such as strain sensors. 294 Supported by this theoretical prediction, He et al 290 applied uniaxial tensile strain along zigzag and armchair directions (Figure 21b) to continuously tune the electronic structure of atomically thin MoS 2 . When strain was loaded to MoS 2 , a red shift in optical absorption could be witnessed along both zigzag and armchair directions due to reduced band gap, as shown in Figure 21c.…”
Section: Effect Of Strain On Energymentioning
confidence: 94%
“…In addition, the electron effective mass was found to be reduced under strain, thus resulting in enhanced carrier mobility. This implies a practical approach for tuning the electrical properties in advanced electronic devices such as strain sensors . Supported by this theoretical prediction, He et al applied uniaxial tensile strain along zigzag and armchair directions (Figure b) to continuously tune the electronic structure of atomically thin MoS 2 .…”
Section: Intrinsic Photonic Properties Of 2d Materialsmentioning
confidence: 96%